Pharmacological Characterization of the Microsomal Prostaglandin E2 Synthase-1 Inhibitor AF3485 In Vitro and In Vivo - Di Francesco, Luigia; Bruno, Annalisa; Ricciotti, Emanuela; Tacconelli, Stefania; Dovizio, Melania; Guillem-Llobat, Paloma; Alisi, Maria Alessandra; Garrone, Beatrice; Coletta, Isabella; Mangano, Giorgina; Milanese, Claudio; FitzGerald, Garret A.; et al. (Frontiers in Pharmacology, 2020)
Rationale. The development of inhibitors of microsomal prostaglandin(PG)E2 synthase-1(mPGES-1) was driven by the promise of attaining antiinflammatory agents with a safe cardiovascular profile because of the possible diversion of the accumulated substrate, PGH2, towards prostacyclin(PGI2). Objectives. We studied the effect of the human mPGES-1 inhibitor, AF3485(a benzamide derivative) on prostanoid biosynthesis in human whole blood in vitro. To characterize possible off-target effects of the compound, we evaluated:(i)the impact of its administration on the systemic biosynthesis of prostanoids in a model of complete Freund's adjuvant(CFA)-induced monoarthritis in rats; (ii) the effects on cyclooxygenase(COX)-2 expression and the biosynthesis of prostanoids in human monocytes and human umbilical vein endothelial cells(HUVECs) in vitro. Methods. Prostanoids were assessed in different cellular models by immunoassays. The effect of the administration of AF3485(30 and 100mg/kg,i.p.) or celecoxib(20mg/kg, i.p.), for 3 days, on the urinary levels of enzymatic metabolites of prostanoids, PGE-M, PGI-M, and TX-M were assessed by LC-MS. Results.In LPS-stimulated whole blood, AF3485 inhibited PGE2 biosynthesis, in a concentration-dependent fashion. At 100μM, PGE2 levels were reduced by 66.06±3.30% associated with a lower extent of TXB2 inhibition(40.56±5.77%). AF3485 administration to CFA-treated rats significantly reduced PGE-M(P<0.01) and TX-M(P<0.05) similar to the selective COX-2 inhibitor, celecoxib. In contrast, AF3485 induced a significant(P<0.05) increase of urinary PGI-M while it was reduced by celecoxib. In LPS-stimulated human monocytes, AF3485 inhibited PGE2 biosynthesis with an IC50 value of 3.03 µM(95% CI:0.5-8.75). At 1μM, AF3485 enhanced TXB2 while at higher concentrations the drug caused a concentration-dependent inhibition of TXB2. At 100μM, maximal inhibition of the two prostanoids was associated with the downregulation of COX-2 protein by 86%. These effects did not involve AMPK pathway activation, IkB stabilization, or PPARγ activation. In HUVEC, AF3485 at 100μM caused a significant(P<0.05) induction of COX-2 protein associated with enhanced PGI2 production. These effects were reversed by the PPARgamma antagonist GW9662. Conclusions.The inhibitor of human mPGES-1 AF3485 is a novel antiinflammatory compound which can also modulate COX-2 induction by inflammatory stimuli. The compound induces also endothelial COX-2-dependent PGI2 production via PPARγ activation, both in vitro and in vivo, which might translate into a protective effect for the cardiovascular system.